BOOK REVIEW: Geoffrey Roberts, “Stalin’s Library. A Dictator and His Books”, Yale University Press, New Haven, 2022, 260 p. - MUREŞAN, Tudor (Studia Universitatis Babeș-Bolyai Historia, 2022)
Stalin’s interest in reading books, the respect and care he offered them can be remarked in one event from the ruler’s family life. When his two sons were studying from an old History textbook and the wind blew some of the fragile pages away, their father was supposed to have told them to go and get them back. Later he also supposedly taught them how to repair the volume, fixing its book spine. Eventually, after the book was whole again, Stalin told them: ‘You did good. Now you know how to treat books’1. The book Stalin’s Library. A Dictator and His Books, written by Geoffrey Roberts, was published for the first time in the year of 2022 at Yale University Press. The author is a British historian and Professor at College Cork University. He is specialized in the history of the Soviet Union and some of his works include Stalin’s General: The life of Georgy Zhukov (2012) or The Soviet Union and the Origins of the Second World War (1995). Some of his ideas come as innovative, but are also difficult to digest for the scientific community and the public. For example, he forwarded the idea that the Soviet Union and Stalin represented an important part in the process of saving liberal democracy together with the communist system, from the danger of Nazism. Also, sentencing the terror and the brutality of the system, Roberts declared that Moscow was responsible for some of the most important achievements of humanity too.